Identification and Ranking of Value Engineering indicators in the projects of the worn-out urban fabric of the North East Investment Company using the Fuzzy Delphi Method - Sayed Amir Reza Madarshahian; Ali Reza Afshari (مهندسی و مدیریت ساخت)
The purpose of this research was to identify the effective indicators in conducting "value engineering" studies in the projects of the worn-out urban fabric of North East Investment Company. For this purpose, previous studies used to identify indicators. Feebly researchers introduced 36 indicators as the main effective factors in value engineering studies. The panel of experts of this research were 20 experts from people involved, active or related to the subject of value engineering studies of Northeast Investment Company. The present study identified and prioritized value-engineering indicators in urban dilapidated fabric projects using the fuzzy Delphi model. To carry out this research, a document study used to identify the value engineering indicators in the urban dilapidated fabric projects and the fuzzy Delphi technique used to prioritize the identified indicators. The survey conducted in three stages and the results of each stage were refined. The panel of research experts included the experts of North East Investment Company. Data collection was done using the fuzzy Delphi method and by sending questionnaires in three stages. To achieve the goals of the research; First, with library studies, value engineering indicators identified in dilapidated urban fabric projects, and then by using the fuzzy Delphi method in three stages and asking for opinions through a five-point Likert scale questionnaire from 20 experts of dilapidated urban fabric projects. 36 items that got a sufficient score in the experts' consensus were determined and then the identified value engineering indicators prioritized using the opinion of experts and based on the fuzzy Delphi method.